Antibacterial, In vitro Lipid per Oxidation and Phytochemical Observation on Achyranthes Bidentata Blume - Devi, P. Uma; Suja, S.; Selvi, S.; Chinnaswamy, P.; Vijayanand, E. (Pakistan Journal of Nutrition, 2007)
The aim of this study is to evaluate the antibacterial efficacy of Achyranthes bidentata against seven different microorganisms such as Escherichia coli, Bacillus subtilin, Proteus vulgaris, Salmonella typhi, Staphylococcus aureus, Pseudomonas species and Klebsiella pneumoniae. The values of zone of inhibition were measured and compared with standard values. All the extracts of root, stem, leaves and flowers showed high sensitive to Proteus, Escherichia coli, Bacillus subtilin, Salmonella typhi, Klebsiella pneumoniae, moderate and less sensitivity to Staphylococcus aureus and Pseudomonas species. The antiperoxidative effect of various parts of Achyranthes bidentata was also done. Goat liver was used as the lipid source. This in vitro evaluation was done by the measurement of thiobarbituric acid reactive substances (TBARS) in the experimental mixtures of tissue homogenates. The results suggest that the ethanolic extracts of Achyranthes bidentata root and flowers possessed significant in vitro lipid peroxidation inhibiting activities, which is possibly attributed to its free radical scavenging properties. All the parts of plant extracts were subjected to qualitative analysis to find out phytoconstituents present in them. Results showed the presence of alkaloids, flavonoids, phenols, and steroids and the absence of saponins, glycosides and tannins.